The Moderating Effect of Accounting Expertise on the Relationship Between Board Characteristics and Earnings Management "Evidence from Iraq" - Sakhil, Ali Dakhil; Bajuri, Norkhairul Hafiz; Hasan, Hussein Falah; Ali, Shireen Tawfeeq (Advances in Social Sciences Research Journal, 2024)
The current study aims to examine how board characteristics impact earnings management in non-financial companies. Its primary objective is to ascertain whether accounting expertise modifies the association between board characteristics and earnings management. The data utilised in this study came from 598 firm-year observations from 46 non-financial sector businesses registered on the Iraqi Stock Exchange between 2010 and 2022. To take care of potential endogeneity and reverse causality, the study employed the system generalised method of moments (SGMM) estimate model. The findings revealed a positive and significant relationship between gender diversity, busyness, board independence, and earnings management. Conversely, the results show that the relationship between board independence, busyness, gender diversity, and earnings management is significantly and negatively moderated by accounting expertise. Thus, by investigating the subject experimentally in Iraq, this study adds to the body of existing literature. Additionally, by investigating whether accounting expertise moderates the association between board features and EM, the study fills the gap in the literature.